Analysis of Osteoclastogenesis/Osteoblastogenesis on Nanotopographical Titania Surfaces. Issue 8 (18th February 2016) - Silverwood, Robert K.; Fairhurst, Paul G.; Sjöström, Terje; Welsh, Findlay; Sun, Yuxin; Li, Gang; Yu, Bin; Young, Peter S.; Su, Bo; Meek, Robert M. D.; Dalby, Matthew J.; Tsimbouri, Penelope M.
Abstract : A focus of orthopedic research is to improve osteointegration and outcomes of joint replacement. Material surface topography has been shown to alter cell adhesion, proliferation, and growth. The use of nanotopographical features to promote cell adhesion and bone formation is hoped to improve osteointegration and clinical outcomes. Use of block‐copolymer self‐assembled nanopatterns allows nanopillars to form via templated anodization with control over height and order, which has been shown to be of cellular importance. This project assesses the outcome of a human bone marrow‐derived co‐culture of adherent osteoprogenitors and osteoclast progenitors on polished titania and titania patterned with 15 nm nanopillars, fabricated by a block‐copolymer templated anodization technique. Substrate implantation in rabbit femurs is performed to confirm the in vivo bone/implant integration. Quantitative and qualitative results demonstrate increased osteogenesis on the nanopillar substrate with scanning electron microscopy, histochemical staining, and real‐time quantitative reverse‐transcription polymerase chain reaction analysis performed. Osteoblast/osteoclast co‐culture analysis shows an increase in osteoblastogenesis‐related gene expression and reduction in osteoclastogenesis. Supporting this in vitro finding, in vivo implantation of substrates in rabbit femora indicates increased implant/bone contact by ≈20%. These favorable osteogenic characteristics demonstrate the potential of 15 nm titania nanopillars fabricated by the block‐copolymer templated anodization technique. Abstract : Attempting to improve osteointegration and long‐term outcomes of implants, titania patterned with 15 nm nano pillars has been assessed in a human bone marrow‐derived osteoblast/osteoclast co‐culture and in a rabbit femora in vivo model. Quantitative and qualitative analysis demonstrates the osteogenic effect of the 15 nm nanopillars, highlighting their potential clinical significance to titanium ortho pedic implants.